Social policy in the face of a global pandemic: Policy responses to the COVID‐19 crisis in Central and Eastern Europe. (26th January 2021) - Aidukaite, Jolanta; Saxonberg, Steven; Szelewa, Dorota; Szikra, Dorottya
Abstract: This article documents and compares the social policies that the governments in Central and Eastern Europe (CEE) implemented to combat the first wave of COVID‐19 pandemic by focusing on Hungary, Lithuania, Poland and Slovakia. Our findings show that governments in all four countries reacted to the COVID‐19 crisis by providing extensive protection for jobs and enterprises. Differences arise when it comes to solidaristic policy responses to care for the most vulnerable population, in which CEE countries show great variation. We find that social policy responses to the first wave of COVID‐19 have largely depended on precious social policy trajectories as well as the political situation of the country during the pandemic.